STRATEGI PENGEMBANGAN AGROINDUSTRI VCO DI KABUPATEN KULON PROGO - Lantarsih, Retno (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
VCO (Virgin Coconut Oil) is a diversified agroindustry products made from coconut. This study aims to design the VCO small agroindustrial development strategy . This study used SWOT (Strength, Weakness, Opportunity, Threat) analysis. The results showed that VCO Agroindustries in the small industries category are in a position of turn around. This position was to overcome weaknesses and to exploit the opportunities available. Keyword: Virgin Coconut Oil, Agroindustry, SWOT Analysis